Submitting to God: Women and Islam in Urban Malaysia by Sylva Frisk (Seattle, WA: University of Washington Press, 2009. pbk. 216 pages) (American Journal of Islam and Society, 2011)
is an interesting and informative study of urban Malay women who haveturned to Islam to regulate their daily lives. While the book focuses onMuslim women, it is written for a broader audience not necessarily familiarwith Islam—namely, anthropologists and feminists. Following SabaMahmoud1 and other recent scholarship on pious Muslim women, Friskargues for the necessity of acknowledging agency not only when it resistsor reinforces patriarchy. Much of feminist writing has recognized women’sagency only when women have actively resisted patriarchy. Otherwise,women are seen as passive victims. Frisk critiques this dichotomous understandingof agency.The aim of Submitting to God is thus to treat pious women as agentsand to understand the meaning of what they do as defined by the womenthemselves (5). Instead of focusing on the effects of Islamization on women’slives, the book’s goal is to account for women’s Islamization—that is,their religiosity and their spiritual development (15). Frisk conducted herfieldwork from 1995 to the present in mosques in Kuala Lumpur’s affluent ...